Temporal Evolution of Myocardial Hemorrhage and Edema in Patients After Acute ST‐Segment Elevation Myocardial Infarction: Pathophysiological Insights and Clinical Implications. Issue 2 (February 2016) - Carrick, David; Haig, Caroline; Ahmed, Nadeem; Rauhalammi, Samuli; Clerfond, Guillaume; Carberry, Jaclyn; Mordi, Ify; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Hood, Stuart; Watkins, Stuart; et al.
Abstract : Background: The time course and relationships of myocardial hemorrhage and edema in patients after acute ST‐segment elevation myocardial infarction (STEMI) are uncertain. Methods and Results: Patients with ST‐segment elevation myocardial infarction treated by primary percutaneous coronary intervention underwent cardiac magnetic resonance imaging on 4 occasions: at 4 to 12 hours, 3 days, 10 days, and 7 months after reperfusion. Myocardial edema (native T2) and hemorrhage (T2*) were measured in regions of interest in remote and injured myocardium. Myocardial hemorrhage was taken to represent a hypointense infarct core with a T2* value <20 ms. Thirty patients with ST‐segment elevation myocardial infarction (mean age 54 years; 25 [83%] male) gave informed consent. Myocardial hemorrhage occurred in 7 (23%), 13 (43%), 11 (33%), and 4 (13%) patients at 4 to 12 hours, 3 days, 10 days, and 7 months, respectively, consistent with a unimodal pattern. The corresponding median amounts of myocardial hemorrhage (percentage of left ventricular mass) during the first 10 days after myocardial infarction were 2.7% (interquartile range [IQR] 0.0–5.6%), 7.0% (IQR 4.9–7.5%), and 4.1% (IQR 2.6–5.5%; P <0.001). Similar unimodal temporal patterns were observed for myocardial edema (percentage of left ventricular mass) in all patients ( P =0.001) and for infarct zone edema (T2, in ms: 62.1 [SD 2.9], 64.4 [SD 4.9], 65.9 [SD 5.3]; P <0.001) in patients without myocardial hemorrhage. Alternatively, in patients with myocardial hemorrhage, infarct zone edema was reduced at day 3 (T2, in ms: 51.8 [SD 4.6]; P <0.001), depicting a bimodal pattern. Left ventricular end‐diastolic volume increased from baseline to 7 months in patients with myocardial hemorrhage ( P =0.001) but not in patients without hemorrhage ( P =0.377). Conclusions: The temporal evolutions of myocardial hemorrhage and edema are unimodal, whereas infarct zone edema (T2 value) has a bimodal pattern. Myocardial hemorrhage is prognostically important and represents a target for therapeutic interventions that are designed to preserve vascular integrity following coronary reperfusion. Clinical Trial Registration: URL:https://clinicaltrials.gov/ . Unique identifier: NCT02072850.